Fatigue life analysis of steel riveted rail bridges affected by corrosion - Macho, Martin (2019)
Decades-old steel bridges have to endure an unfavourable environment that causes the ageing and deterioration of material properties. Moreover, railway bridges in particular are exposed to a large number of stress ranges that may lead to fatigue damage. The combination of both phenomena has a significant impact on the condition of bridges and their remaining service life. In such cases, appropriate maintenance or even removal of the deteriorated structure is necessary; however, a lack of funds often makes this difficult. The subject of this paper is the development of methodology for the assessment of remaining service life of existing steel bridges considering the fatigue and corrosion effects. Using MATLAB (R) software, a program for the prediction of the remaining fatigue life has been developed. The results of earlier experiments and numerical simulations were integrated into this tool. Various scenarios regarding the future maintenance of bridges were included in the program, thus making it possible to calculate the remaining service life of bridges, including corresponding costs. The second half of the paper presents a case study demonstrating the application of the methodology and the calculation program.